2022
DOI: 10.3389/fnut.2022.965911
|View full text |Cite
|
Sign up to set email alerts
|

Causal associations between dietary antioxidant vitamin intake and lung cancer: A Mendelian randomization study

Abstract: BackgroundOxidative stress is currently considered to be closely related to the occurrence of respiratory tumors, especially lung cancer. Many observational studies have shown that increased antioxidant intake can reduce the risk of lung cancer, but the results are still controversial. Therefore, we performed a two-sample Mendelian randomized (MR) analysis to clarify the causal relationship between antioxidant vitamins and lung cancer.MethodsTo assess the causal effect of dietary antioxidant vitamin intake on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 79 publications
0
11
1
Order By: Relevance
“…For example, we replicated a largely null effect of circulating retinol that was previously suggested using MR on the odds of Alzheimer’s disease 71 , digestive tract cancers 72 , 73 , and endometrial cancer 74 . Interestingly, a previous MR study did report weak evidence of a risk increasing relationship between genetically proxied dietary intake of retinol and lung cancer, which was the opposite direction of that we found for measured circulating retinol in this study 75 . However, MR studies of dietary retinol intake are very difficult to interpret due to the pleiotropic nature of any genetic effects on nutrient intake patterns that would be used as IVs, highlighting the importance of GWAS using measured retinol.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, we replicated a largely null effect of circulating retinol that was previously suggested using MR on the odds of Alzheimer’s disease 71 , digestive tract cancers 72 , 73 , and endometrial cancer 74 . Interestingly, a previous MR study did report weak evidence of a risk increasing relationship between genetically proxied dietary intake of retinol and lung cancer, which was the opposite direction of that we found for measured circulating retinol in this study 75 . However, MR studies of dietary retinol intake are very difficult to interpret due to the pleiotropic nature of any genetic effects on nutrient intake patterns that would be used as IVs, highlighting the importance of GWAS using measured retinol.…”
Section: Discussioncontrasting
confidence: 99%
“…This study employed the multiplicative random-effects inverse variance weighted (IVW) method as the primary approach for conducting MR analysis to evaluate the genetic association between OSA and VTE. The IVW method meta-analyzes the Wald ratio estimates for each SNP on the outcome, providing precise estimates of causal effects when all selected SNPs are valid IVs [24]. However, the estimates of causal effects from the IVW method may be biased by the influence of pleiotropic IVs.…”
Section: Discussionmentioning
confidence: 99%
“…The IVW method metaanalyzes the Wald ratio estimates for each SNP on the outcome, providing precise estimates of causal effects when all selected SNPs are valid IVs. 24 However, the estimates of causal effects from the IVW method may be biased by the influence of pleiotropic IVs. To ensure the validity and robustness of the results, sensitivity analyses were implemented using three additional MR methods, namely MR-Egger, weighted median, and MR pleiotropy residual sum and outlier (MR-PRESSO).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dietary antioxidant supplementation has been linked to adverse effects and in some cases increases the risk of lung disease. For instance, studies have reported that lung cancer incidence was increased following β-carotene [ 84 , 85 , 86 ] and retinol supplementation [ 87 ]. Given the common environmental and genetic risk factors underlying both lung cancer and COPD [ 88 ], these findings suggest that these supplements may also exert harmful effects in COPD.…”
Section: Non-targeted Antioxidants In Copdmentioning
confidence: 99%
“…Given the common environmental and genetic risk factors underlying both lung cancer and COPD [ 88 ], these findings suggest that these supplements may also exert harmful effects in COPD. This may be due to the possibility that dietary antioxidant supplementation may interfere with the absorption, transport, and metabolism of carotenoids and other micronutrients, thus increasing the risk of lung cancer [ 87 , 88 ]. In particular, higher concentrations of antioxidants have been suggested to be detrimental (reviewed in [ 89 ]).…”
Section: Non-targeted Antioxidants In Copdmentioning
confidence: 99%